Proposta formativa de ensino da escrita: o investimento na devolutiva - Reis, Juliana Pagliarelli dos (2022)
Writing is a complex process in which meaning is produced by mobilizing different linguistic and expressive features. Consequently, its teaching and evaluation also involves high complexity. Producing a text at school should be an exercise of reflection based on interlocutive situations created during class – something quite distant from a simple reproductive task or a mechanical act. For that, a teacher of the Portuguese language needs to assume the role of mediator of the written production of students in a consistent undertaking guided by a theoretical-methodological approach which should emphasize their intervention in all stages of writing – not only the correction of the final product by simply grading it – drawing on the assumption of formative evaluation. The focus of this evaluation process is the organization and reorientation of the pedagogical work by giving feedback in order to improve students’ learning. Considering this, the question of this research is defined as: how to construct a formative approach of the teaching of writing which may allow teachers of the Portuguese language to give out more detailed and profound feedback on texts produced by students? In order to answer this question, the general aim is to show a formative approach of the teaching of writing, parting from specialized literature on the topic, with an emphasis on the formative feedback for the correction and evaluation of the students’ written production. The specific aims are: 1) differentiate writing as a product from writing as a process and the concepts associated with these uptakes; 2) examine evaluation as learning and its formative potential with a focus on the role of feedback in implementing this evaluation process. Theoratically, this research draws support from academic work which approaches the teaching of writing in a processbased outlook fundamented on social interactionism as well as on literature on evaluating as learning. This survey classifies as qualitative documental research and unfolds into a more propositional perspective by constructing an educational proposition of writing with a focus on formative feedback. The featured proposition is structured as an integrated pedagogical project of text production and the study of Natural Science topics by first year students of secondary school